KAJIAN URAIAN TUGAS UNIT APRON MOVEMENT CONTROL DI TERMINAL 1 BANDAR UDARA INTERNASIONAL JUANDA SURABAYA - Elin Prima Pebriani; Ika Endrawijaya (Langit Biru: Jurnal Ilmiah Aviasi, 2019)
Along with the increasing movement of aircraft in Surabaya Juanda International Airport Terminal 1, the demand for garbarata services as a facility provided for service users has increased. Therefore the Apron Movement Control unit must carry out its two functions both the service function and the air side supervision optimally. This research was compiled based on observations regarding the task description of the Apron Movement Control unit under the Air Side Operations Department in the implementation of the service and supervision functions. The AMC unit in carrying out its job descriptions is more focused on the service function, especially the garbarata service. This has an impact on the oversight function by the AMC unit that is not running optimally so that it affects the violations in the air side. By fulfilling the needs of AMC Terminal 1 human resources, the division of work areas, and the application of strict sanctions are expected to make both AMC unit functions run optimally and minimize the level of violations to ensure the security and safety of flight operations at Juanda International Airport, Surabaya